Evaluation of Cost and Time Estimates Using The Earned Value Method: A Case Study of The Construction of RU Guest House and Main House - Komang Gede Triska Bayu Wedananta; Hanie Teki Tjendani; Budi Witjaksana (International Journal Labs, 2025)
This study evaluates the performance of the RU Guest House and Main House construction project in Bali, focusing on time and cost estimates using the Earned Value Method (EVM). By analyzing the Actual Cost of Work Performed (ACWP), Budgeted Cost of Work Performed (BCWP), and Budgeted Cost of Work Scheduled (BCWS), the study identifies significant delays and cost overruns. The project, initially scheduled for 34 weeks, experienced a 27.99% delay by week 21, with an estimated cost increase of IDR 1,079,046,375. The findings reveal that poor initial planning and logistical constraints, such as narrow access roads for material delivery, contributed to the delays. The study also forecasts an extended completion time of 42 weeks and provides estimates for the total project cost at IDR 13,736,136,610. The results highlight the importance of thorough planning and logistics management to minimize risks. EVM proved to be an effective tool in monitoring and controlling project performance, providing essential insights for improving future project management practices. The study concludes that better planning, logistics, and real-time project performance monitoring are crucial to ensuring project success in both time and budget management.